2015
DOI: 10.3109/17538157.2014.948171
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the digital divide: A systematic review of eHealth literacy in underserved populations in the United States

Abstract: eHealth provides an important mechanism to connect medically underserved populations with health information, but little is known about gaps in eHealth literacy research in underserved adult populations within the U.S. Between June and July 2013, three systematic literature reviews of five databases were conducted and a subsequent hand search was completed. Identified literature was screened and studies meeting exclusion and inclusion criteria were synthesized and analyzed for common themes. Of the 221 article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
218
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(246 citation statements)
references
References 41 publications
21
218
2
5
Order By: Relevance
“…Previous suggestions have also indicated that self-management approaches, particularly those incorporating cognitive behavioral principles, may be more appropriate for higher SES individuals. 9, 10, 17 Consequently, identifying and addressing barriers that low SES patients commonly encounter such as low health knowledge or literacy 6, 13, 70, 72 is appealing as it has potential to enhance LBP treatment outcomes for this often underserved patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous suggestions have also indicated that self-management approaches, particularly those incorporating cognitive behavioral principles, may be more appropriate for higher SES individuals. 9, 10, 17 Consequently, identifying and addressing barriers that low SES patients commonly encounter such as low health knowledge or literacy 6, 13, 70, 72 is appealing as it has potential to enhance LBP treatment outcomes for this often underserved patient population.…”
Section: Discussionmentioning
confidence: 99%
“…On a population level, a proper measurement instrument could provide insight into vulnerable subgroups that face additional challenges in using health care, due to its digitization. For example, previous studies have shown that digital health literacy is related to sociodemographics such as age, education, and income [4,9,10], and studies have shown that certain populations do not have the skills and knowledge to use Web-based health tools for their own benefit and might thereby even become underserved [5,10]. Better insight into populations at risk of low digital health literacy can lead to development and tailoring of health technologies for these specific groups [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…While pamphlets may still be present in some dentists’ offices, our findings should be directly applicable to other health communication channels. The separate effects of deep and surface structures can inform research and application in areas such as the nascent field of health apps for mobile devices (Hingle & Patrick, 2016) and the growing dissemination of health information on the internet (Chesser, Burke, Reyes, & Rohrberg, 2016; Viswanath & Kreuter, 2007). In addition, health messages on social media (Gibbons, Fleisher, Slamon, Bass, Kandadai, & Beck, 2011; Smith & Denali, 2014) should not miss the opportunity to enhance their culturally sensitive messages with appropriately congruent images.…”
Section: Resultsmentioning
confidence: 99%